Pricing Policies for Quantity Discounts - Dada, Maqbool; Srikanth, K. N. (Management Science, 1987)
In this paper we analyze the seller's decision to offer quantity discounts to the buyer. We build on an existing model as follows. We first characterize the range of order sizes and prices which reduce costs for the buyer and seller, and develop related pricing schemes. The model is then extended to allow inventory carrying costs to be a function of price.